If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T(n + -1T) = -1S Reorder the terms: T(-1T + n) = -1S (-1T * T + n * T) = -1S (-1T2 + nT) = -1S Solving -1T2 + nT = -1S Solving for variable 'T'. Reorder the terms: S + -1T2 + nT = -1S + S Combine like terms: -1S + S = 0 S + -1T2 + nT = 0 The solution to this equation could not be determined.
| 8(6x-7)=0 | | X+-7=8 | | 40(x-20)=10x+40 | | [2y-7]=13 | | 7r+5=5r+35 | | t2u2r/rut3 | | 16y/4-81 | | C=-22x+-x^2 | | 3v+9-11v=-23 | | 2^5/3 | | 3/4 | | -6+2s=-9+5 | | 3x=ln(4) | | w+2w+18w=0 | | 26=5x+3x+2 | | -3x+2=x-2 | | 5y-3xy-8=0 | | 100/95*x/875 | | -10s=7 | | 100/95*X/875=.05 | | 40x=48x | | (-2)=3 | | x+6y-52=-7 | | 23y/6-5y/2=8 | | x+(-9)=-2 | | [8x]=72 | | 5x-15+1=5x-14 | | 1.1/9 | | 93=3x+18 | | 4^4/3 | | 6u=7u-9 | | 30=6t^2+6t |